Convergence of Inner Iterations Scheme of the Discrete Ordinate Method in Spherical Geometry (Journal of Computational Mathematics, 2005)
In transport theory, the convergence of the inner iteration scheme to the spherical neutron transport equation has been an open problem. In this paper, the inner iteration for a positive step function scheme is considered and its convergence in spherical geometry is proved.